TESTING OBSOLESCENCE IN FIXED ASSETS. - Nelson, Oscar S. (The Accounting Review, 1945)
Abstract Fixed assets are, in a sense, deferred charges to operations. It is from this viewpoint that they should be valued on the balance sheet of a "going concern."Recently there has been a change in emphasis on the part of accountants from the balance sheet to the income statement. In line with this change of emphasis, fixed assets should be given balance-sheet values in line with their efficiency as producing agents. The efficiency of each fixed asset has to be determined by its comparison with other available assets that could be utilized to perform the same service. The sacrifice of depreciation and interest having been made at the outset, an asset value is set up on the balance sheet. It is thus evident that the balance sheet amount is the present value of future periodic charges on account of depreciation and interest. If it is desired that the periodic charges for depreciation and interest total the same for each period, the compound interest or annuity method of computing depreciation and interest should be used.